A study on the effectiveness of promotion strategies towards 1ASLAH at Bank Rakyat Kota Belud / Ahmad Fauzi Saiffuddin - Saiffuddin, Ahmad Fauzi (2010)
This study is entitled "THE STUDY ON THE EFFECTIVENESS OF PROMOTION STRATEGIES AT BANK RAKYAT KOTA BELUD ". Promotion strategies are the basic element that must exist in order to make a products success in the market. Without good promotion strategies, I would be very difficult to a company to market their product smoothly. Since in the banking industry have a very tight competition, Bank Rakyat should have an excellent promotion strategies in order to make them to reach their customers effectively. Thus, Bank Rakyat is look forward to find ways to improve their promotion on 1Aslah. As part of that, a feedback from the respondent are taken and analyzed by the researcher. The significant of this study will give good impact especially to the Bank Rakyat Kota Belud, then to the respondents and lastly to the researcher as well. In this study, two types of data collection are used. There are primary and secondary data. Primary data are collected through the questionnaire that had answered by the respondents (customers) and secondary data are collected from the several sources that are relevant to this study such as reference books, internet website and Bank Rakyat magazine. There are two types of secondary data that used in this study which includes internal and external data. Internal data is referring to the data that gathered from the organization where the research is carried out such as the Annual report and magazines. While, external data is refer to the data collected outside the organization such as from the internet, projects paper and the published document that already exist for reference. Based on the finding and analysis, the researcher had found the conclusion and several recommendations towards improving the current promotion strategies on 1Aslah for Bank Rakyat Kota Belud.